Rituximab as the first-line treatment in newly diagnosed systemic lupus erythematosus - Haiting Wang; Haiting Wang; Liling Zhao; Shaoying Yang; Huihua Ding; Wanlong Wu; Liqin Yu; Jiajia Jin; Nan Shen; Qiong Fu; Shuang Ye (Frontiers in Immunology)
ObjectivesRituximab (RTX) has been commonly used for the treatment of patients with severe or refractory systemic lupus erythematosus (SLE), yet real-world data concerning RTX as the first-line treatment in newly diagnosed moderate-to-severe SLE patients is lacking.MethodsWe conducted a retrospective cohort study using a newly diagnosed (<3 months) hospitalized Systemic Lupus Inception Cohort (hSLIC) at our center between April 1, 2013 and September 1, 2022. All patients were followed up for at least 12 months or until death. The cohort included patients on RTX (n = 104) as the first-line treatment and those on conventional immunosuppressants (IS) (n = 154) as comparators. Propensity-score-based inverse probability of treatment weighting (IPTW) was used to minimize possible confounding factors. The primary outcome analyses included attainment of modified lupus low disease activity state (mLLDAS) and remission by 12 months. The secondary outcomes focused on mortality, major flare rates, and the incidence of adverse events of interest, i.e., major infections.ResultsAfter IPTW, 76.0%/50.5% of RTX-treated patients achieved mLLDAS/remission versus 45.8%/9.7% in the conventional IS group during 12 months of follow-up, respectively (p = 0.005 and p < 0.001). The sensitivity analyses with renal or neuropsychiatric lupus removal and timeline breakout (pre- versus post-November 2019) confirmed the robustness of RTX’s efficacy in achieving mLLDAS and remission outcomes. Additionally, the incidence of major infections was similar between the two groups (12.5% vs. 8.4%, p = 0.288).ConclusionsIn patients with newly diagnosed moderate-to-severe SLE, upfront treatment with RTX was associated with improved clinical outcomes compared to conventional immunosuppressive therapy in terms of achieving low disease activity or remission by 12 months.